Rainastar Irrigation Project and its Impact on Paddy Cultivation in Chakratirtha Village Development Committee Lamjung District, Nepal - Dhital, Netra Prasad (The Third Pole: Journal of Geography Education, 2014)
Present paper has been focused on the changing aspects of paddy cultivation of Chakratir the VDC, Lamjung district after the implementation of Rain star Irrigation Project (RIP). The RIP is confined in 7 wards of the VDC, where only 3 and 4 wards are not covered. The study of changing scenario of paddy cultivation after the completion of RIP has been mainly based on the primary data. The study has found that various crops such as paddy, maize and millet were grown almost equally in the study area before the availability of irrigation facility. Due to the availability of irrigation facility, the crop production has been moved towards paddy cultivation. Paddy has become the most important crop for consumption and income. Before irrigation project only 204 ha lands was occupied for paddy production whereas after the construction of the Project it was extended to 340 ha land. DOI: http://dx.doi.org/10.3126/ttp.v13i0.11541 The Third Pole Vol. 13, 2013 page : 12-16